Pengembangan Keterampilan Sosial dan Kolaborasi Mahasiswa melalui Metode Peer Teaching di Perguruan Tinggi - Nida Aulia Faridah; Anggela Pratama Chandra; Della Amelia (EDUTECH, 2023)
Educational institutions, particularly universities, played a pivotal role in enhancing the skills required by students. One of the approaches that universities could adopt was utilizing teaching methods that fostered the growth and improvement of essential skills. This study aimed to examine the influence of peer teaching methods on the development of students' social and collaborative skills. A quantitative research method was employed, using a survey-based approach. The research subjects consisted of 105 samples, comprising active students from the University of Education Indonesia, selected through quota sampling. Data collected were analyzed using simple linear regression analysis. The obtained research findings indicated that the implementation of peer teaching methods significantly correlated with and exerted an influence on enhancing students' social and collaborative skills. These results demonstrated that the application of peer teaching methods facilitated the development of these skills among students. The method established an environment conducive to inter-student interaction, facilitating communication, and nurturing empathetic abilities. The utilization of peer teaching methods assisted students in learning to work effectively within teams, providing mutual support, and sharing knowledge. This approach could be applied within the realm of education to aid students in honing their social skills for day-to-day interactions and collaborative abilities crucial in the professional sphere. The study offered insights into the potential of peer-based teaching as a tool to elevate the social and collaborative facets of students, thereby making a positive contribution to preparing them for future challenges.